Regional Labour Standards in the SADC: Is It Possible, Given the EU Experience? - Smit, Paul (Journal of Law, Society and Development, 2015)
Globalisation and the increasing movement of capital and labour across international borders, with the exception of migrant workers who are facing major obstacles due to immigration laws, are creating a situation where laws in general and labour laws in particular are acquiring an international character. International bodies such as the United Nations, the International Labour Organisation and the European Union have adopted various international norms and standards to which most countries have agreed and which have established minimum international standards for basic universal human rights and worker rights. The Southern African Development Community is a transnational organisation that has also adopted certain basic norms and standards in its Treaty, Charter on Fundamental Social Rights and various protocols that are applicable to all citizens within the Community. In this contribution, the concept of transnational labour relations is considered. The different international approaches towards transnational labour relations are evaluated, as is the manner in which the European Union approached the integration of regional labour standards. The author seeks to establish what the Southern African Development Community can learn from the European Union’s experience and in what way a transnational labour relations system or regional labour standards regime for the Southern African Development Community can be established.
Keywords: Regional integration; Transnational labour relations (TNLR); international law; labour rights; regional labour standards; social rights

Employee participation and voice in companies: a legal perspective - Botha, Monray Marsellus (North-West University, 2015)
Recently, South African company law underwent a dramatic overhaul through the introduction of the Companies Act 71 of 2008. Central to company law is the promotion of corporate governance: companies no longer are accountable to their shareholders only but to society at large. Leaders should direct company strategy and operations with a view to achieving the triple bottom-line (economic, social and environmental performance) and, thus, should manage the business in a sustainable manner. An important question in company law today: In whose interest should the company be managed? Corporate governance needs to address the entire span of responsibilities to all stakeholders of the company, such as customers, employees, shareholders, suppliers and the community at large. The Companies Act aims to balance the rights and obligations of shareholders and directors within companies and encourages the efficient and responsible management of companies. The promotion of human rights is central in the application of company law: it is extremely important given the significant role of enterprises within the social and economic life of the nation. The interests of various stakeholder groups in the context of the corporation as a “social institution” should be enhanced and protected. Because corporations are a part of society and the community they are required to be socially responsible and to be more accountable to all stakeholders in the company. Although directors act in the best interests of shareholders, collectively, they must also consider the interests of other stakeholders. Sustainable relationships with all the relevant stakeholders are important. The advancement of social justice is important to corporations in that they should take into account the Constitution, labour and company law legislation in dealing with social justice issues. Employees have become important stakeholders in companies and their needs should be taken into account in a bigger corporate governance and social responsibility framework. Consideration of the role of employees in corporations entails notice that the Constitution grants every person a fundamental right to fair labour practices. Social as well as political change became evident after South Africa's re-entry into the world in the 1990s. Change to socio-economic conditions in a developing country is also evident. These changes have a major influence on South African labour law. Like company law, labour law, to a large extent, is codified. Like company law, no precise definition of labour law exists. From the various definitions, labour law covers both the individual and collective labour law and various role-players are involved. These role-players include trade unions, employers/companies, employees, and the state. The various relationships between these parties, ultimately, are what guides a certain outcome if there is a power play between them. In 1995 the South African labour market was transformed by the introduction of the Labour Relations Act 66 of 1995. The LRA remains the primary piece of labour legislation that governs labour law in South Africa. The notion of industrial democracy and the transformation of the workplace are central issues in South African labour law. The constitutional change that have taken place in South Africa, by which the protection of human rights and the democratisation of the workplace are advanced contributed to these developments. Before the enactment of the LRA, employee participation and voice were much-debated topics, locally and internationally. In considering employee participation, it is essential to take due cognisance of both the labour and company law principles that are pertinent: the need for workers to have a voice in the workplace and for employers to manage their corporations. Employee participation and voice should be evident at different levels: from information-sharing to consultation to joint decision-making. Corporations should enhance systems and processes that facilitate employee participation and voice in decisions that affect employees. The primary research question under investigation is: What role should (and could) employees play in corporate decision-making in South Africa? The main inquiry of the thesis, therefore, is to explore the issue of granting a voice to employees in companies, in particular, the role of employees in the decision-making processes of companies. The thesis explores various options, including supervisory co-determination as well as social co-determination, in order to find solutions that will facilitate the achievement of employee participation and voice in companies in South Africa.
Keywords: CSR; Collective bargaining; Corporate Social Responsibility; Corporate governance; Corporate law; Disputes; Economic democracy; Employee participation; Empowerment; Fairness; Industrial democracy; Joint decision-making; Labour law; Matters of mutual interest; Shareholders; Social justice; Stakeholders; Workplace forums

Labour rights and working conditions in corporate codes of conduct: an assessment of the legal dimension, in different national contexts, of selected multinational corporations’ corporate social responsibility commitments - Tiemeni, Thierry Galani (University of the Western Cape, 2015)
At the heart of this thesis is the notion of Corporate Social Responsibility (CSR), an innovative concept deep-rooted in the globalisation phenomenon. The notion of CSR entails the much-debated duty of businesses, not only to comply with international and local standards in terms of, inter alia, labour rights and working conditions, human rights and environmental protection, but also to be at the forefront of voluntary and uplifting actions geared toward addressing societal issues and concerns. For corporations, it is about moving from the traditional approach of business as an activity with the sole purpose of realising profit towards acknowledging the need to integrate societal and environmental issues and concerns into their business purposes. The thesis examines selected multinational corporations’ (MNC) approaches to CSR as contained in their codes of conduct, in an effort to reach a comprehensive understanding of the purpose, interest and practices of businesses engaging in CSR activities. Particular attention is given to the analysis of labour orientated measures implemented by selected MNCs as they undertake to voluntarily act as proponents of the theory of the necessity of socially responsible businesses. The aim is to comparatively assess the legal dimension and the relevance, in different countries, of these MNC CSR commitments. The first part of the thesis is theoretical and has the purpose to present a comprehensive analysis of CSR against the current legal framework, at a global scale and within the context of selected countries. The thesis will explore the notion of CSR in order to present its definition and characteristics, briefly retrace its history, differentiate it from related and/or similar concepts, and finally assess the extent of its introduction and adaptation into various national and international institutional frameworks. Even though initially addressing the issue of CSR in the current legal framework as a whole, the scope of the thesis will ultimately be reduced to focus only on labour-related aspects of CSR. The aim of the thesis is to assess MNC’s CSR commitments, and subsequently highlight the interaction between CSR, labour and employment legal frameworks (at national and international level) and the effective implementation of labour rights and working conditions as observed in the context of different countries. More importantly, the thesis will also include a comparative analysis of CSR principles included in selected MNC codes of conduct, in order to assess the extent of their compliance with national labour legislation, international labour standards, as well as the standards and principles set by national and international CSR instruments and institutions. The purpose of such an exercise is to thoroughly assess the impact of a national context - in terms of national legal, economic, social and industrial framework - on the legal dimension, and the relevance of MNCs CSR commitments. A crucial argument developed in the thesis refers to the fact that MNC codes of conduct may have the potential to impact on labour rights and working conditions of a MNC across the different countries into which the MNC operates. Finally, considering the fact that as a topic CSR is a potentially controversial subject, it is necessary to point out, from the onset, that the thesis engages with the subject from a critical perspective. The approach therefore entails critically analysing and discussing MNC commitments and practices as observed in different countries, so as to be able to ascertain and comprehend the impact of a national context on the content, the relevance and the legal dimension of MNC codes of conducts
Keywords: Code of conduct; Corporate Social Responsibility; Labour rights; Multinational corporations; Working conditions